Long‐term surveillance biopsy: Is it necessary after pediatric heart transplant?. (1st December 2018) - Peng, David M.; Ding, Victoria Y.; Hollander, Seth A.; Khalapyan, Tigran; Dykes, John C.; Rosenthal, David N.; Almond, Christopher S.; Sakarovitch, Charlotte; Desai, Manisha; McElhinney, Doff B.
Abstract: Due to limited and conflicting data in pediatric patients, long‐term routine surveillance endomyocardial biopsy (RSB) in pediatric heart transplant (HT) remains controversial. We sought to characterize the rate of positive RSB and determine factors associated with RSB‐detected rejection. Records of patients transplanted at a single institution from 1995 to 2015 with >2 year of post‐HT biopsy data were reviewed for RSB‐detected rejections occurring >2 year post‐HT. We illustrated the trajectory of significant rejections (ISHLT Grade ≥3A/2R) among total RSB performed over time and used multivariable logistic regression to model the association between time and risk of rejection. We estimated Kaplan‐Meier freedom from rejection rates by patient characteristics and used the log‐rank test to assess differences in rejection probabilities. We identified the best‐fitting Cox proportional hazards regression model. In 140 patients, 86% did not have any episodes of significant RSB‐detected rejection >2 year post‐HT. The overall empirical rate of RSB‐detected rejection >2 year post‐HT was 2.9/100 patient‐years. The percentage of rejection among 815 RSB was 2.6% and remained stable over time. Years since transplant remained unassociated with rejection risk after adjusting for patient characteristics (OR = 0.98; 95% CI 0.78‐1.23; P = 0.86). Older age at HT was the only factor that remained significantly associated with risk of RSB‐detected rejection under multivariable Cox analysis ( P = 0.008). Most pediatric patients did not have RSB‐detected rejection beyond 2 years post‐HT, and the majority of those who did were older at time of HT. Indiscriminate long‐term RSB in pediatric heart transplant should be reconsidered given the low rate of detected rejection.